Characteristics of typhoon activity in the coastal area of North center Region, Vietnam in the period 1960-2013 - Thuy, Hoang Luu Thu; Co, Nguyen Thanh; Hang, Phan Thi Thanh; Tuan, Tong Phuc (Vietnam Journal of Earth Sciences, 2016)
Typhoon data during period 1960-2013 at JMA ((Japan Meteorological Agency) was used for analysis the typhoon activity characteristics in the coastal area of Northern Center Region Vietnam. The result showed that, there were about 1,5 typhoons have passed or strong affected to the study area annually. The typhoon season is from July to October, and the frequency was highest in September (Avg. 0,6 typhoon/y) and secondly in October (Avg. 0,4 typhoon/y). The trend of typhoon occurrence was reducing during period 1960-2013. During ENSO’s years, the number of typhoon in La Nina years were twice higher than in La Niño years. The decade 80’ was reached highest number of typhoon, and also the highest number of strong typhoon among 5 recent decades. References Vũ Thanh Hằng, Ngô Thị Thanh Hương, Phan Văn Tân, 2010: Đặc điểm hoạt động của bão ở vùng biển gần bờ Việt Nam giai đoạn 1945-2007, Tạp chí Khoa học ĐHQGHN, Khoa học Tự nhiên và Công nghệ 26, Số 3S, tr.344-353. Nguyễn Đức Ngữ, 2008: Biến đổi khí hậu, Nxb. Khoa học và Kỹ thuật, 388tr. Nguyễn Đức Ngữ, Nguyễn Trọng Hiệu, 2013: Khí hậu và Tài nguyên khí hậu Việt Nam, Nxb. KH-KT, 294tr. Nguyễn Văn Lượng, 2013: Sử dụng thông tin KT-TV phục vụ phát triển KT-XH khu vực BTB, tạp chí Khí tượng - Thủy văn, Số 631/2013, tr.4-6. Phan Văn Tân, 2010: Nghiên cứu tác động của BĐKH toàn cầu đến các yếu tố và hiện tượng khí hậu cực đoan ở Việt Nam, khả năng dự báo và giải pháp chiến lược ứng phó, Chương trình KHCN cấp NN, MS: KC08.29/06-10, 398tr. Nguyễn Văn Tuyên, 2007: Xu hướng hoạt động của xoáy thuận nhiệt đới trên Tây bắc Thái Bình Dương và Biển Đông theo các cách phân loại khác nhau, Tạp chí Khí tượng Thủy văn 559. tr.4-10. Đinh Văn Ưu, Phạm Hoàng Lâm, 2005: Biến động mùa và nhiều năm của trường nhiệt độ mặt nước biển và sự hoạt động của bão tại khu vực Biển Đông, Tạp chí Khoa học ĐHQGHN, Khoa học Tự nhiên và Công nghệ XXI 3PT, 127. Đinh Văn Ưu, 2009: Đánh giá quy luật biến động dài hạn và xu thế biến đổi số lượng bão và áp thấp nhiệt đới trên khu vực Tây Thái Bình Dương, Biển Đông và ven biển Việt Nam, Tạp chí Khoa học ĐHQGHN, Khoa học Tự nhiên và Công nghệ, 25, 3S, 542. Christopher W. Landsea, 1993: A climatology of intense (or major) Atlantic hurrcanes. Monthly Weather Review, Vol. 121, pp. 1703-1713. William M. Gray, John D. Sheaffer and Christopher W. Landsea, 1997: Climate trends associated with multi-decadal variability of Atlantic hurricanes activity. Hurricanes: Climate and Socioeconomic Impacts. H.F. Diaz and R.S. Pulwarty, Eds., Springer-Verlag, New York, pp.15-53. C.W. Landsea, R. A. Pielke, A. M. Mestas-Nuñez, J. A. Knaff, 1999: Atlantic basin hurricanes: Indices of climatic changes, Climatic Change 42, pp 89-129. S.B. Goldenberg, C.W. Landsea, A.M. Mestas-Nuñez, W.M. Gray, 2001: The recent increase in Atlantic hurricance activity: causes and implications, Science 293, pp.474-479. J.C.L. Chan, J.E. Shi, 1996: Long-term trends and interannual variability in tropical cyclone activity over the western North Pacific, Geophys. Res. Lett. 23, pp.2765-2767. J.C.L. Chan, J.E. Shi, 2000: Frequency of typhoon landfall over Guangdong Province of China during the period 1470-1931, Int. J. Climatol. Volume 20, Issue 2, pp.183-190. http://www.jma.go.jp/jma/indexe.html.